Prediction of the Linear and Nonlinear Optical Properties of a Schiff Base Derivatives via DFT - Clodoaldo Valverde; Ítalo Nuta Ribeiro; João Victor B. Soares; Basílio Baseia; Francisco A. P. Osório (Advances in Condensed Matter Physics)
In this work, the density functional theory (DFT) calculation combined with a polarizable continuum model (PCM) was used to study the solvent media effects on the electrical and geometrical behaviors of the Schiff-base derivative, (E)-4-[({4-[(pyridin-2-ilmetilideno)amino]phenyl}amino)-metil]fenol (EPAF). The linear and nonlinear optics parameters, as the dipole moment, linear polarizability, and first and second hyperpolarizabilities, were calculated at DFT/B3LYP/6-311+G(d) level, for the EPAF molecule in several solvent media. The dynamic behavior of the Hyper-Rayleigh Scattering (HRS) first hyperpolarizability was studied as function of the electric field frequency. The results presented for HRS first hyperpolarizability suggest that the studied crystal has good nonlinear optical properties. In addition, the gap energy was calculated from the HOMO-LUMO energies difference in several solvent media. The EPAF crystal intermolecular interactions were studied by the Hirshfeld surface analysis. The third-order electric susceptibility χ(3) of the crystal EPAF was also calculated, indicating the EPAF crystal as a promising candidate for NLO applications in photonic and optoelectronic devices.